Congestion Charge Analysis for Private Vehicle Users in the Central Business District (Case Study: Jalan Pemuda-Pandanaran-Ahmad Yani, Semarang City) - Utami, Adita; Qumara, Nadhiyah Ayu; Nurhidayat, Asep Yayat (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2023)
Semarang, part of the Kedungsepur area, has a population of 1,656,564 with an average annual growth of 1.57%. The increase in population can increase the intensity of trips, so good transportation infrastructure is needed. The presence of the Central Business District (CBD) area in Semarang, precisely on Jalan Pemuda-Pandanaran-Ahmad Yani, often results in congestion. The purpose of this research was to provide recommendations for solutions in the form of a study on applying congestion charges to private vehicles to overcome congestion on the road. This research uses traffic analysis to determine the performance of existing roads using the PKJI 2014 method. After knowing the traffic performance, modeling the mode selection of private cars for BRT Trans Semarang was carried out using the logit binomial difference method. In this study, three travel attributes were considered influential in the choice of mode: travel time, congestion costs, and frequency. The private car utility equation for BRT Trans Semarang is obtained with a value of U=-11.3774-0.2639(X1)-0.0120(X2)-1.5403(X3). Based on the research results, a congestion charge of IDR 10,000 was obtained, with the percentage of private car users switching to BRT Trans Semarang at 79.8%. So implementing a congestion charge is considered adequate to reduce the congestion on the road.ABSTRAKKota Semarang merupakan bagian dari kawasan Kedungsepur memiliki 1.656.564 jiwa penduduk dengan pertumbuhan rata-rata tiap tahun sebesar 1,57%. Peningkatan jumlah penduduk tersebut berpotensi meningkatkan intensitas perjalanan, sehingga dibutuhkan sarana prasarana transportasi yang baik. Adanya Central Business District (CBD) kawasan di kota Semarang tepatnya di Jalan Pemuda-Pandanaran-Ahmad Yani sering mengakibatkan kemacetan. Sehingga tujuan penelitian ini dilakukan untuk memberikan rekomendasi solusi berupa kajian penerapan congestion charge terhadap kendaraan mobil pribadi, untuk mengatasi kemacetan lalu lintas di Jalan tersebut. Diawali dengan melakukan analisis lalu lintas untuk mengetahui kinerja ruas jalan eksisting dengan metode PKJI 2014. Selanjutnya setelah diketahui kinerja lalu lintasnya, dilakukan pemodelan pemilihan moda mobil pribadi terhadap BRT Trans Semarang dengan metode logit binomial selisih.  Penelitian ini menggunakan 3 atribut perjalanan yang dinilai berpengaruh dalam pemilihan moda yaitu waktu tempuh, biaya kemacetan, dan frekuensi. Didapatkan persamaan utilitas mobil pribadi terhadap BRT Trans Semarang dengan nilai U = - 11.3774 - 0.2639 (X1) - 0.0120 (X2) - 1.5403 (X3). Nilai congestion charge diperoleh Rp.10.000 dengan persentase pengguna mobil pribadi yang akan berpindah menggunakan BRT Trans Semarang sebesar 79,8%. Sehingga adanya skenario penerapan congestion charge dinilai cukup efektif untuk menurunkan tingkat kemacetan dijalan tersebut.